How the body works - Smith, Ginny; Temple, Nicola (Dorling Kindersley Limited, 2016)
Helps you to understand how our bodies keep us alive and thriving and get to the bottom of such niggling questions as why we get dizzy, why we get butterflies in our stomachs, and why we get jetlag! This title shows how the human body and brain works.